Comparing the Effects of Auditory Deprivation and Sign Language within the Auditory and Visual Cortex - Fine, Ione; Finney, Eva M.; Boynton, Geoffrey M.; Dobkins, Karen R. (Journal of cognitive neuroscience, 2005)
To investigate neural plasticity resulting from early auditory deprivation and use of American Sign Language, we measured responses to visual stimuli in deaf signers, hearing signers, and hearing nonsigners using functional magnetic resonance imaging. We examined “compensatory hypertrophy” (changes in the responsivity/size of visual cortical areas) and “cross-modal plasticity” (changes in auditory cortex responses to visual stimuli). We measured the volume of early visual areas (V1, V2, V3, V4, and MT+). We also measured the amplitude of responses within these areas, and within the auditory cortex, to a peripheral visual motion stimulus that was attended or ignored. We found no major differences between deaf and hearing subjects in the size or responsivity of early visual areas. In contrast, within the auditory cortex, motion stimuli evoked significant responses in deaf subjects, but not in hearing subjects, in a region of the right auditory cortex corresponding to Brodmann's areas 41, 42, and 22. This hemispheric selectivity may be due to a predisposition for the right auditory cortex to process motion; earlier studies report a right hemisphere bias for auditory motion in hearing subjects. Visual responses within the auditory cortex of deaf subjects were stronger for attended than ignored stimuli, suggesting top-down processes. Hearing signers did not show visual responses in the auditory cortex, indicating that cross-modal plasticity can be attributed to auditory deprivation rather than sign language experience. The largest effects of auditory deprivation occurred within the auditory cortex rather than the visual cortex, suggesting that the absence of normal input is necessary for large-scale cortical reorganization to occur.